Arteria Lusoria - Griffiths, Bradley; Doubell, Anton (SA Heart Journal, 2017)
A 54-year-old man with cardiovascular risk factors of diabetes mellitus and smoking was referred to our cardiology department after experiencing an episode of chest pain the previous day, which resolved spontaneously prior to arrival at his local hospital. His electrocardiogram showed a Wellen’s Type B pattern suggesting a proximal left anterior descending coronary artery culprit lesion, and his troponin I level confirmed a non-ST elevation myocardial infarction.